Reviews in fluorescence 2009 - Geddes, Chris D.; SpringerLink (Online service). (New York Springer, 2011)
Reviews in Fluorescence 2009, the sixth volume of the book serial from Springer, serves as a comprehensive collection of current trends and emerging hot topics in the field of fluorescence and closely related disciplines. It summarizes the year?s progress in fluorescence and its applications, with authoritative analytical reviews specialized enough to be attractive to professional researchers, yet also appealing to the wider audience of scientists in related disciplines of fluorescence. Reviews in Fluorescence offers an essential reference material for any lab working in the fluorescence field and related areas. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource.    offers an essential reference material for any lab working in the fluorescence field and related areas. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource.       ? Key features · Chapters authored by known leading figures in the fluorescence field. · New volume publishes annually · Comprehensive coverage of the year?s hottest and emerging topics. · Accessible utility in a single volume reference. · Reviews in Fluorescence 2009 topics include: · Hot electron-Induced Electrogenerated Chemiluminescence · Time-correlated, single-photon counting methods in endothelial cell mechanobiology. · Origin of Tryptophan Fluorescence · Protein Folding, Unfolding and Aggregation Processes revealed by Rapid Sampling of Time-Domain Fluorescence. Chapters authored by known leading figures in the fluorescence field. · New volume publishes annually · Comprehensive coverage of the year?s hottest and emerging topics. · Accessible utility in a single volume reference. · Reviews in Fluorescence 2009 topics include: · Hot electron-Induced Electrogenerated Chemiluminescence · Time-correlated, single-photon counting methods in endothelial cell mechanobiology. · Origin of Tryptophan Fluorescence · Protein Folding, Unfolding and Aggregation Processes revealed by Rapid Sampling of Time-Domain Fluorescence.
Metal Enhancement of Near-IR Fluorescence for Molecular Biotechnology Applications -- Principal Component Global Analysis of Series of Fluorescence Spectra -- Hot Electron -Induced Electrogenerated Chemiluminescence -- Extension of Fluorescence Response to the Near IR-Region -- Luminescence analysis of Bi4(TiO4)3 and LiZnVO4 ceramic powders -- Time-correlated, single-photon counting methods in endothelial cell mechanobiology -- Going beyond continuous glucose monitoring with boronic acid appended bipyridinium salts -- Mapping and immunomodulation of the cell surface protein architecture with therapeutic implications: Fluorescence is a key tool of solution -- Origin Of Tryptophan Fluorescence -- Protein Folding, Unfolding and Aggregation Processes revealed by Rapid Sampling of Time-Domain Fluorescence -- Theme and Variation on N-Aryl-1,8-Napthalimides: Minimal Modification to Red shifted fluorescence and applications in Fluorescent Chemosensors -- Z-scan fluorescence correlation spectroscopy ? a powerful tool for determination of lateral diffusion in biological systems -- Total Internal Reflection With Fluorescence Correlation  Spectroscopy.
Electronic reproduction.
Keywords: Fluorescence; Electronic books